Correlation between Structure Characteristics and Pair Radial Distribution Function in Silica Glass under Compression - Lan, Mai Thi (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4304, 2018)
Abstract: We have studied structure of silica glass at different pressures and temperature of 300K by using Molecular Dynamics simulation (MD) method. The model consists of 6000 atoms (2000 Si, 4000 O atoms) with the periodic boundary condition. We applied the Morse-Stretch potentials which describe the pairwise interactions between ions for SiO 2 system. There is structural phase transformation from tetrahedra (SiO 4 ) to octahedra (SiO 6 ) network structure. There is splitting in the Si-Si pair radial distribution function (PRDF) at high pressure (100 GPa). The original of this splitting relates to the edge- and face-sharing bonds. The new second peak of the O-O PRDF at the high pressure originates from oxygen atoms of the edge-sharing bonds. Thus, there is rearrangement of O atoms. O atoms have tendency to more order arrangement that leads to form some oxygen hcp and fcc structure in the model at high pressure. Keywords: Molecular Dynamics simulation (MD), Silica (SiO2), Structure, the peak splitting. References [1] W. Zachariasen, J. Am. Chem. Soc. 54, pp. 3841–3851(1932) [2] Mozzi và Warren, J. App. Cryst. 2, pp. 164–172 (1969) [3] Jin W, Kalia RK, Vashishta P, Phys Rev B. 50:118–131 (1994) [4] Sato T, Funamori N. Phys Rev B. 82, 184102 (2010) [5] Trachenko K, Dove MT. J Phys Condens Matter. 14:7449–7459 (2002) [6] Inamura Y, Katayama Y, Utsumi W, Phys Rev Lett. 93, 015501 (2004). [7] P. K. Hung, N. V. Hong, and L. T. Vinh, J. Phys.: Condens. Matter 19, 466103 (2007). [8] Vollmayr-Lee K, Zippelius A, Phys Rev E. 88:052145 (2013) [9] P. Tangney and S. Scandolo, .J. Chem. Phys.117, 8898 (2002). [10] P. K. Hung, N. V. Hong, and L. T. Vinh, J. Phys.: Condens. Matter 19, 466103 (2007). [11] A. Zeidler, K. Wezka, R. F. Rowlands, D. A. J. Whittaker, P. S. Salmon, A. Polidori, J. W. E. Drewitt, S. Klotz, H. E. Fischer, M. C. Wilding, C. L. Bull, M. G. Tucker and M. Wilson, Phys. Rev. Lett. 113, 135501 (2014). [12] L. I. Tatarinova, in The Structure of Solid Amorphous and Liquid Substances (Nauka, Moscow, 1983). [13] M. Guerette, M. R. Ackerson, J. Thomas, F. Yuan, E. B. Watson, D. Walker and L. Huang, Sci. Rep. 5, 15343 (2015). [14] W. Jin, R. K. Kalia, and P. Vashishta, Phys. Rev. B 50, 118 (1994). [15] J. S. Tse, D. D. Klug, Y. L. Page, Phys. Rev. B 46, 5933 (1992).